Analisis SWOT pemetaan media tentang halal lifestyle di Indonesia dengan NVivo: Studi literatur review - Bagaskara, Doni Yusuf; Rohmadi, Rohmadi (Nur Science Institute, 2024)
This research aims to determine a SWOT analysis regarding Halal Lifestyle Consumption Behavior in Indonesia using the NVivo approach. This research uses qualitative methodology with the NVivo approach and literature review.